College of Arts and Sciences Graduates’ Performance: A Tracer Study - Camuyong, Christian Sam F.; Decena, Cyrem F.; Reyes, Karl Christian; Malong, Michael R.; Gregorio, Maria Chello L.; Magtalas, Santi A.; Adlawan, Jarele E. (Future Science / FSH-PH Publications, 2023)
The current undertaking aimed to trace the employability of Bachelor of Science in Biology and Bachelor of Science in Psychology graduates of a State University in Central Luzon, Philippines from 2005 to 2020. Descriptive- quantitative research design was utilized in order to describe and trace the participants’ demographic profile, employment status, and their professional development. Graduates' personal, educational and employment background, as well as their perception to the relevance of the baccalaureate degree in their employment were collected using a survey- questionnaire anchored from CHED’s graduate tracer instrument. The study gathered data from 173 graduates through convenience sampling. Electronic survey forms were used in gathering the data and utilized SPSS version 23 for statistical analysis. Consequently, the collected data revealed that 94.7% of the participants were employed and 67% of them perceived that their degree is relevant to their employment. Lastly, the graduates reported that communication skills were the main contributory skill to their employment developed by their respective programs, while collaborative skills were the most useful.